2020
DOI: 10.1007/s11664-020-08371-9
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Adsorption and Intercalation in Bilayer Graphene Doped with B, N, Si and P: A First-Principles Study

Abstract: Heteroatom-doped graphene is a potential anode material in sodium-ion batteries (SIBs). However, understanding the mechanisms of Na adsorption on the surface and intercalation in the interlayer remains a critical challenge to develop a suitable heteroatom-doped graphene anode. In this work, the structural and electronic influences in B-, N-, Si-and P-doped bilayer graphene (BLG) have been investigated by first-principles calculations. Pyridinic N, graphitic B and Si-doped BLG have preferential adsorption for N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In Eq (1), where E B-CNTNa E B-CNT represent the Na adsorption energies on CNT with and without boron doping. The isolated Na atom energy is represented by E Na .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Eq (1), where E B-CNTNa E B-CNT represent the Na adsorption energies on CNT with and without boron doping. The isolated Na atom energy is represented by E Na .…”
Section: Resultsmentioning
confidence: 99%
“…However, the application of LIBs is suffering from several issues, such as cost, safety, low-temperature performance, and lifetime. Due to the abundant resource reserves and small electrochemical equivalent, SIBs have been regarded as potential candidates [1]. Nevertheless, the Na has larger radius, which suggests insertion and extraction of rapid ions have challenged SIBs development.…”
Section: Introductionmentioning
confidence: 99%
“…Since this article primarily focuses on the utilization of BGP-x to simulate micropores with different pore sizes and ensure a consistent pore size, the edge carbon atoms of BGP-x were fixed. The previous work conducted by our research group 30,41 and other researchers 42,43 has demonstrated that nitrogen doping does not alter the shape of the upper layer of graphene, which retains its planar structure. However, phosphorus-doping can cause a change in the planar structure of the upper layer of graphene due to the larger bond length of the C−P bond (1.76 Å 44 ) compared to the C−C bond (1.43 Å 44 ).…”
Section: Computational Detailsmentioning
confidence: 86%
“…This approach has received significant attention. Zeolites [20][21][22], kaolinite [23][24][25], magnetite [25], graphene [26,27], coal-based materials [28] and resins [27,[29][30][31] are widely used for Na + and K + removal. Adsorbents produce a large amount of waste that needs to be disposed.…”
Section: Introductionmentioning
confidence: 99%